Collection of Excretory/Secretory Products from Individual Developmental Stages of the Blood Fluke Schistosoma mansoni - Leontovyč, Adrian; Ulrychová, Lenka; Horn, Martin; Dvořák, Jan (Methods in molecular biology, 2020)
Individual developmental stages of blood fluke Schistosoma mansoni excrete or secrete a different set of molecules. Here we describe optimized protocols for collection of excretory/secretory products (E/S products) from cercariae, schistosomula, adult worms, and eggs. These E/S products are essential for successful parasitism functioning at the host-parasite interface, enabling invasion into the host and contributing to the survival of the parasite by modulation of host physiology and immune responses. Collection of sufficient amounts of E/S products is required for detailed research of these processes.
Keywords: zvířata; Animals; odběr biologického vzorku; Mice; Ovum; stadia vývoje; Cercaria; Schistosoma mansoni; myši; ovum; Specimen Handling; játra; cerkárie; Life Cycle Stages; Liver